Introduction: The “Ontological Turn” in Russian Anthropology: Turning towards Materiality, Nonhuman Agency, and Hybridity - Sokolovskiy, Sergei (Anthropologica, 2022)
The authors in this thematic issue reflect on the current “ontological turn” in Russian social sciences and humanities, and especially on the influence the turn exerts on various anthropological sub-disciplines and research domains. This introduction reviews publications in Russian academic journals, article collections, theses, books, and book chapters that best illustrate current ontological preoccupations in Russian anthropology. The ontological turn encompasses diverse interests and topics and is often labelled as “material,” “object-oriented,” “speculative-realist,” or “praxiographic.” In fact, we are dealing with multiple interdisciplinary “turns” that intersect and overlap, while interlinking many domains of the biological sciences, geographical sciences, social sciences, and humanities. In Russia, the ontological turn (actor-network theory, material semiotics, symmetrical anthropology, sociology of translation, object-oriented ontology, speculative realism) unfolds in different domains of research that can be grouped into four main fields: 1) medical anthropology, body studies, and death studies; 2) urban anthropology; 3) anthropology of science and techno-anthropology; 4) museum anthropology and material culture studies. The contributions to this issue illustrate current research in medical anthropology, body and death studies, urban anthropology, technoanthropology, museum studies, as well as Siberian ethnography using the perspectivist model.